1989
DOI: 10.1103/physrevlett.62.2092
|View full text |Cite
|
Sign up to set email alerts
|

Infrared divergence of the resonant Raman-Compton scattering

Abstract: The infrared divergence of the resonant Raman-Compton scattering has been studied in collisions of photons on atomic L electrons in the intermediate-momentum-transfer regime. Low-energy continua emitted by Zr atoms, excited, in the vicinity of the K edge, by the monochromatized x rays delivered by the LURE Synchrotron Radiation Facility, have been observed on very thin targets and compared with the theoretically predicted infrared divergence of the Raman scattering. The characteristic change in shape of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 9 publications
(4 reference statements)
0
16
0
Order By: Relevance
“…Although theory unambiguously predicts the infrared divergence, there are no convincing experimental observations. While some measurements were reported of the observed infared divergence (Spitale and Bloom, 1977;Basavaraju et al, 1987;Briand et al, 1989), they were later challenged by others Franck, 1989, 1990) or withdrawn, suggesting that the reported results were perhaps due to other phenomena such as bremsstrahlung following photoeffect. Manninen et al (1990) later observed an infrared rise, but concluded that it was due entirely to photoelectron bremmsstrahlung in the target.…”
Section: Article In Pressmentioning
confidence: 49%
“…Although theory unambiguously predicts the infrared divergence, there are no convincing experimental observations. While some measurements were reported of the observed infared divergence (Spitale and Bloom, 1977;Basavaraju et al, 1987;Briand et al, 1989), they were later challenged by others Franck, 1989, 1990) or withdrawn, suggesting that the reported results were perhaps due to other phenomena such as bremsstrahlung following photoeffect. Manninen et al (1990) later observed an infrared rise, but concluded that it was due entirely to photoelectron bremmsstrahlung in the target.…”
Section: Article In Pressmentioning
confidence: 49%
“…The inclusion of C K stops the cross-sections from diverging as E in approaches B K . This behaviour has been clearly noticed in the measured KL radiative RRS distributions [10,25,26]. Taking this energy-dependence, the present measured cross-section can be used for a first-order estimate of RRS cross-sections at higher energies approaching B K = 90.526 keV.…”
Section: Resultsmentioning
confidence: 73%
“…The excited atom can relax by means of a radiative (resonant Raman scattering) or a nonradiative process (the Auger resonant Raman effect [2]). According to the final state of the excited electron (i.e., into a discrete unoccupied bound state or into the continuous energy band above the Fermi level, in which the available energy is mutually shared in a continuous way among the electron and the scattered photon), the phenomenon has been distinguished by some authors as resonant Raman and resonant Raman-Compton scattering, respectively [3,4]. However, in many cases the discrete bound states merge into the continuum bands and/or when low-resolution spectrometers are used these two different scattering mechanisms cannot be separated.…”
Section: Introductionmentioning
confidence: 99%
“…Up until now several studies have been accomplished related to the systematic determination of the RRS cross sections for transition metals and rare-earth elements by means of synchrotron radiation, x-ray tubes coupled with crystal monochromators, and radioactive or proton-induced x-ray beams [3,4,[16][17][18][19][20][21][22][23][24][25][26]. Nevertheless, despite the important role played by low-Z elements such as Mg, Al, and Si in new materials (e.g., as impurities in silicon wafers) studies of these elements have been rather scarce.…”
Section: Introductionmentioning
confidence: 99%